(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Once the SITI company was created (1992) by Anne Bogart and Tadashi Suzuki, it became usual to talk about the Suzuki-Viewpoints method. However, some younger artists are unaware of the production of those researches, prior to the partnership. The purpose of this article is to present some characteristics of the early days of what was considered the Suzuki method in 1965, when he created the Waseda Shogekijo (Small Waseda Theatre), until the arrival of his company in Toga. The proposal is not to reconstruct his biography, but to investigate what follows in movement in Suzuki’s thought/action, such as the invention of theatrical heterotopias that affect, in different ways, the contemporary Japanese scene, and his singular notion of energy as technology of communication.